Monitoring Menstrual Health Knowledge: Awareness of Menstruation at Menarche as an Indicator - Julie Hennegan; Julie Hennegan; Zay Yar Swe; Kyu Kyu Than; Calum Smith; Lidwien Sol; Hilda Alberda; Justine N. Bukenya; Simon P. S. Kibira; Fredrick E. Makumbi; Kellogg J. Schwab; Peter S. Azzopardi; et al. (Frontiers Media S.A., 2022)
As initiatives to support menstrual health are implemented globally, monitoring progress through a set of comprehensive indicators provides important feedback to direct policies and programs. One proposed core indicator is awareness of menstruation at menarche. That is, at the time of menarche an adolescent girl knowing that menstrual bleeding is something she will experience. In this investigation, we undertook secondary analysis of data collected across four studies to support interpretation of this indicator. We (1) describe the proportion of each sample aware of menstruation at menarche, (2) test variations in awareness according to sociodemographic characteristics, and (3) describe the associations between this indicator and self-reported experience at menarche, social support, and confidence to manage menstruation. Studies included cross-sectional survey data from 421 schoolgirls in Magway, Myanmar, 537 schoolgirls in Soroti, Uganda, 1,359 schoolgirls in Netrokona, Bangladesh, and 599 adult women working in Mukono, Uganda. Awareness of menstruation at menarche varied from 84% in Myanmar to 34% in Bangladesh. Older age at menarche was associated with awareness. Awareness at menarche was not associated with household poverty in the adolescent samples, but greater poverty was associated with lower levels of awareness among adult women. In Myanmar, girls aware of menstruation had significantly higher odds of reporting that they felt prepared (2.85 95% CI 1.34-6.08), happy (OR = 3.81 95% CI 1.74-8.37) and knew what was happening at menarche (OR = 2.37 95% CI 1.34-4.19). However, they also reported higher levels of embarrassment (OR = 1.76 95% CI 1.04-2.97) and did not report significantly less fear (OR = 1.24 95% CI 0.82-1.85). Awareness of menstruation at menarche was associated with higher scores on a menstrual knowledge quiz in both Myanmar (b = 9.51 95% CI 3.99-15.04) and Bangladesh (b = 4.78 95% CI 1.70-7.87). In these studies girls aware of menstruation at menarche also had higher odds of reporting they felt confident discussing menstruation with support sources and managing menstruation at school, while these differences were not significant among schoolgirls in Uganda. Findings support the usefulness of awareness of menstruation at menarche as an indicator to describe minimal knowledge of menstruation and suggest that awareness may signal greater knowledge, social support, and confidence in some settings.